Pengaruh Motivasi, Komitmen dan Reward Pegawai Terhadap Efektivitas Kerja Pegawai Rumah Sakit Nasional Guido Valadares Dili Timor Leste - Domingos Soares; Joaquim Pinto (Program Pascasarjana Universitas Gajayana, 2018)
The purpose of this study is to asses and analyzes the influence of the motivation, commitment and reward staff on work effective. This study adapted the quantitatif study methode or explanatory research study, and the population and sample in this study was doctor, nurses and midwifery were worked on the inpatient ward in Dili National Hospital Guido Valadares Dili Timor-Leste about 71 persons, data collection technique used the questioner and than use the multiple linear regression analysis and to show the f test and t test. Regarding with the result of the multi regression analysis find out formulation bellow: Y = -5,142 + 0,115 X1 +0,425 X2 + 0,576 X3 + 3,644. From formulation result above can discused that have influences independent variable and dependent variable. And other regarding with the F test and t test showed that level of significant F test is 0,000. Regarding with this result to be summary that Motivation, commitment and reward variable simultant give influences to working effectively health care in Dili National hospital. In other side t test, find that have partial each independent variable are motivation, commitment and reward have significant influence to work effective are motivation is 0,047 < , (5%), commitment is 0,425 <, (5%) and reward is 0,000 <, (5%) with the t table = 2,000. And next regarding with calculation find out reward variable have most dominant influence to work effective compared with the motivation and commitment variable.